Shear Stress Regulates Adhesion and Rolling of CD44+ Leukemic and Hematopoietic Progenitor Cells on Hyaluronan - Christophis, Christof (The Biophysical Society, 2011)
Leukemic cells and human hematopoietic progenitor cells expressing CD44 receptors have the ability to attach and roll on hyaluronan. We investigated quantitatively the adhesion behavior of leukemic cell lines and hematopoietic progenitor cells on thin films of the polysaccharides hyaluronan and alginate in a microfluidic system. An applied flow enhances the interaction between CD44-positive cells and hyaluronan if a threshold shear stress of 0.2 dyn/cm(2) is exceeded. At shear stress ∼1 dyn/cm(2), the cell rolling speed reaches a maximum of 15 μm/s. Leukemic Jurkat and Kasumi-1 cells lacking CD44-expression showed no adhesion or rolling on the polysaccharides whereas the CD44-expressing leukemic cells KG-1a, HL-60, K-562, and hematopoietic progenitor cells attached and rolled on hyaluronan. Interestingly, the observations of flow-induced cell rolling are related to those found in the recruitment of leukocytes to inflammatory sites and the mechanisms of stem-cell homing into the bone marrow.